Estatística no nono ano do ensino fundamental a partir de uma abordagem histórico-cultural na perspectiva de Vygotsky - Carvalho, Emerson Pereira de (2023)
This research is based on the need for Statistics teaching aimed at promoting the appropriation of the meanings of concepts from a historical-cultural perspective. To this end, it takes as a theoretical framework Lev Semenontich Vygotsky's Historical-Cultural Theory and structures a set of activities associated with the appropriation of the meaning of Statistics concepts. From this perspective, this study aims to answer the following question: What contributions are provided to students by supporting the teaching of Statistics in Vygotsky's historical-cultural approach? The objective is to develop, apply and evaluate a didactic sequence structured in the Vygotskian perspective to address Statistics content in the ninth grade of Elementary School. The Didactic Sequence presents content in line with the National Common Curricular Base (BNCC), with application in 12 class periods - six meetings of two periods. These meetings are structured in five stages that seek to favor central aspects of Vygotsky's historical-cultural perspective, namely: recovery of spontaneous knowledge; discussion of the concept under study through the structuring action of the teacher mediated by teaching strategies or tools; carrying out activities to apply the concept in experiential and socially contextualized situations; carrying out activities of cooperation, sharing and socialization; activities to apply knowledge. The locus of application is a group of students in the ninth grade of Elementary School in a full-time school in the public education network of the state of Rondônia. The research assumes the qualitative approach and the understanding of pedagogical intervention research announced by Damiani et al.(2012), involving the production of data from the logbook entries of the researcher, who is the teacher himself, and the materials produced by the students during the meetings. As a result, the study pointed to the viability of the proposal in didactic terms, highlighting the contributions to the construction of meanings of the concepts addressed within an approximation between the spontaneous and the scientific; to the process of social interaction marked by the exchanges and sharing among the participants mediated by the activities carried out, as well as between them and the experiential world and present in their family context; and to the process of social awareness and freedom brought about by the proposal and strongly marked by the dialectic that guided the meetings. The educational product developed refers to the didactic sequence developed and applied in the study, serving as support material for Elementary School Mathematics teachers - Final Years. This educational product is available on the EduCapes Portal (http://educapes.capes.gov.br/handle/capes/741798).